Toward an international law of renewable energies - Benzaghou, Naziha; Gueribiz, Mourad; Maidi, Naïma (The International tax journal, 2025)
Studying the topic “Toward an international law of renewable energies” is important for establishing a unified international legal framework to regulate the use and development of renewable energy sources. The article points to the environmental and economic challenges posed by excessive dependence on fossil fuels, highlighting the need to transition to clean and sustainable energies. It also discusses the absence of binding international legal texts that organize cooperation among states in this field, which hampers sustainable development efforts. The article calls for an international treaty dedicated to renewable energies that would include rules for technology transfer, financing for developing countries, and ensuring climate justice. It also stresses the importance of the role of international and regional organizations in coordinating efforts and setting unified technical standards. The article concludes by affirming that laying down an international law for renewable energy is a decisive step to confront climate change and achieve fair and comprehensive global energy security.